ICT learning and its butterfly effects on students’ academic performance - S. Kumar, Adarsh; S. Anil, Akhila; L, Bhanupriya; Jyothilakshmy, H (International Journal of Engineering and Technology, 2018)
In this knowledge driven era, there exist a tight competition among the students. High academy performance is a key factor, which evaluates a person’s knowledge and eligibility criteria for higher studies. Teaching method has an impact on student’s learning behavior and performance. Introduction of ICT learning has created a massive change in the education sector. This research is focused on the influencing effect of ICT learning among the student community. For which, we are introducing an APM (Academic Performance Management) proposing that ICT learning technique has a greater impact on student performance through developing subject interest among students.